Mortality rate of percutaneous coronary interventions in ST-segment elevation myocardial infarction patients under the public health insurance schemes of Thailand - Chumsantivut, Suppavit; Lertmaharit, Somrat; Rattananupong, Thanapoom; Lertsuwunseri, Vorarit; Athisakul, Siriporn; Wanlapakorn, Chaisiri; Srimahachota, Suphot (Frontiers in Cardiovascular Medicine, 2024)
Background In Thailand, access to specific pharmaceuticals and medical devices for ST-elevation myocardial infarction (STEMI) patients is restricted within certain healthcare systems, leading to inequalities in the quality of medical care among different healthcare systems. This study aims to compare mortality rates within one year of STEMI patients among the public health insurance schemes of Thailand. Methodology This study is a single-center retrospective analysis of patients with STEMI treated with primary percutaneous coronary intervention (pPCI). It involves patients utilizing various state health insurance schemes in Thailand from January 1, 2010, to December 31, 2020. Data collection occurred through the hospital's computerized management system and the registration administration office of the Department of Provincial Administration. Results The study involved 1,077 patients, categorized into three groups based on their state health insurance: Universal Health Coverage (UC) (546 patients, 50.7%), Social Security System (SS) (199 patients, 18.5%), and Civil Service Reimbursement (CS) (332 patients, 30.8%). The one-year mortality rates in these groups were 10.57%, 4.21%, and 6.47%, respectively (p = 0.010). In the unadjusted model, the SS group showed a lower risk of one-year mortality [Hazard Ratio (HR) 0.38, 95% CI 0.18–0.80, p = 0.011], and the CS group also demonstrated a lower risk (HR 0.59, 95% CI 0.35–0.99, p = 0.047) compared to the UC group. In the adjusted model, only the CS group significantly reduced the risk of one-year mortality. Other factors that affected one-year mortality were age ≥65 years, prior coronary artery diseases, Killip class 3–4, pre-discharge prescription of angiotensin-converting enzyme inhibitors, occlusion in the left anterior descending artery, multivessel disease, in-hospital atrial fibrillation/flutter and in-hospital pericardial effusion. Conclusion Healthcare schemes play a significant role in influencing one-year mortality rates among STEMI patients treated with pPCI. This information would be crucial for developing strategies and programs to aid healthcare policymakers at both regional and international levels in reducing morbidity and mortality.